Effect of Osmotic Pressure Gradient on Concentration of Treated Tannery Effluent in Forward Osmosis - Sayyad, Sameer; Kazmi, Absar (ASEAN Journal of Chemical Engineering, 2024)
In this study, Forward Osmosis (FO) process is investigated for concentrating three different types of synthetic secondary treated tannery effluents (FS1, FS2 and FS3) as feed solution and using NaCl solution as draw solution. Operating FO at low osmotic pressure gradient (∆Πlow) of 9.33 ± 0.7 bars and high osmotic pressure gradient (∆Πhigh) of 20.63 ± 0.7 bars, for concentration of FS1, FS2, and FS3 respectively, was evaluated in terms of flux (Jw), flux decline ratio (FDR), percentage increase in feed solution concentration (CF) and solute rejection (SR). Results show that operating FO at ∆Πhigh gave higher Jw and lower FDR as compared to operating FO at ∆Πlow, irrespective of feed solution composition. However operating FO at ∆Πlow provided higher Jw and lower FDR for FS1 (4.54 LMH and 36.1%) as compared to FS2 (4.15 LMH and 40.9%) and FS3 (3.20 LMH and 45.35%) whereas operating FO at ∆Πhigh provided higher Jw and lower FDR for FS3 (6.18 LMH and 26.88%) and FS2 (6.16 LMH and 27.84%) as compared to FS1 (5.7 LMH and 32.52%). CF and SR were higher for experiments performed at ∆Πhigh as compared to ∆Πlow, irrespective of feed solution composition. Solutes like magnesium and chromium had good rejection (>80%) at ∆Πhigh and ∆Πlow, irrespective of FS type. Potassium and Ammonium had low rejection at ∆Πhigh and ∆Πlow for FS3, FS2 and FS1 respectively. Essentially, by emphasizing osmotic pressure gradient as a critical component, this study suggested a methodical strategy to researching the FO process.